THE ROLE OF WORK SKILLS AND DIGITALIZATION IN THE RELATIONSHIP BETWEEN GASTRONOMY INVOLVEMENT, LOCAL FOOD CONSUMPTION VALUE, AND PURCHASE INTENTION OF MALANG'S CULINARY SPECIALTIES - Liza Lidyana; Ike Kusdyah Rachmawati; Yunus Handoko (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This study was conducted in the city of Malang, involving 230 respondents who are local culinary enthusiasts. The analysis technique used is SmartPLS to examine the relationships between gastronomy involvement, Local Food Consumption value, culinary skills, digitalization, and purchase intention. The results show that Gastronomy Involvement does not have a direct effect on purchase intention. However, this involvement positively influences culinary skills and digitalization, indicating that increased engagement in gastronomy can enhance skills and the utilization of digital technology. Additionally, Local Food Consumption value significantly affects both culinary skills and digitalization.Culinary skills have been shown to positively impact purchase intention, emphasizing the importance of skill development in enhancing consumer buying intentions. Meanwhile, digitalization does not exhibit a direct effect on purchase intention. The study also found that both Gastronomy Involvement and Local Food Consumption can increase purchase intention through culinary skills, but not through digitalization. These findings provide important insights for culinary industry stakeholders in Malang to focus on skill development as a strategy to enhance purchase intention.